Modelagem e otimização de manobras em processos de perfuração de poços de petróleo e gás - Slongo, Juliano Scholz (2018)
The control of pressure gradients generated by drilling string's movements during tripping operations is a great challenge to be overcome. High axial velocities imposed on the drill string can generate sufficiently large pressure gradients that bring well inner pressure to overtake safe limits defined by formation's pore and fracture pressures, resulting in loss of resources, damage to the porous reservoir and risk of accidents. On the other hand, the adoption of conservative policies concerning the axial velocity of the drill string results in underutilization of the installed infrastructure, large periods of operation and increase in non-productive time, meaning a waste of operational and financial resources. This work presents an optimization model based on a mathematical formulation for the compressible and transitory flow resulting from the tripping operations. The process modeling is based on the conservation equations of mass and momentum that are solved through the method of the characteristics. The domain of the problem is represented by two pipes with different diameters, representing the well and the drill pipe, concentrically positioned. Both flows inside the drilling column and into the annular space are represented. Nevertheless, the use of a drill bit or any other installed equipment along the column is not considered. The upper ends of the drill string and the annular space are considered open to the atmosphere and the level of fluid within the well is constant. The fluid is considered as a high viscosity Newtonian ones. It's mean that fluid's properties such as compressibility, viscosity and yield stress characteristics are taken as constants. The flow is modeled as one-dimensional, laminar and isothermal, in which the viscous effects are evaluated through the concept of friction factor. The existence of gravel or hydrocarbon inflow is disregarded. Simulations are performed to verify the effects of velocity and acceleration on the pressure gradients experienced. The effects of well geometry and rheological properties of the drilling fluid are also analyzed. The results show that acceleration of the drill string is directly related to the pressure variation rate along the well, whereas the velocity is related to the magnitude of the pressure peak. Increases in the depth of the well, the viscosity of the drilling fluid and the narrowing of the annular space make the pressure gradients larger and the energy dissipation from pressure wave happens so much faster. The optimization model was effective in reducing the operating time and while respect the imposed restrictions.